Quantum photonics sensing in biosystems - Ekaterina Moreva; Valeria Cimini; Ilaria Gianani; Ettore Bernardi; Paolo Traina; Ivo P. Degiovanni; Marco Barbieri (APL Photonics)
Quantum sensors emerged among quantum technologies as the ones with promising potential applications in the near future. This perspective reviews two leading quantum sensing platforms and their advancements toward biological applications: quantum light sources and color centers in diamonds. Quantum light, including squeezed states and N00N states, allows enhanced phase measurements by surpassing the classical shot noise limits. This advantage can be exploited in several contexts, enabling improved resolution and sensitivity, which are particularly valuable in biological contexts where traditional high-intensity illumination could damage or alter delicate samples. In parallel, color centers in diamonds, specifically nitrogen-vacancy and silicon-vacancy centers, also emerged as promising for sensing applications due to their high sensitivity and biocompatibility. These sensors enable detailed intracellular measurements, such as temperature detection, and show potential for measuring magnetic fields of biological origin. Despite these advancements, significant challenges remain in translating these technologies from a controlled laboratory environment to practical, widely applicable devices for diverse biological applications. Overcoming these challenges is crucial for unlocking the full potential of quantum sensors in the biological field.